2016
DOI: 10.1186/s13104-016-2092-5
|View full text |Cite
|
Sign up to set email alerts
|

Low level lead exposure and pregnancy outcomes in an observational birth cohort study: dose–response relationships

Abstract: BackgroundNational and international guidelines on safe levels for blood Pb in pregnancy focus on a threshold above which exposure is of concern. However, it has recently been suggested that the decrease in birth weight per unit increase in blood Pb is actually greater at lower than at higher concentrations of Pb without evidence of a lower threshold of effect. Our aim was to investigate whether there was evidence for a differential effect of maternal Pb levels on birth outcomes and/or a threshold value for ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…Given the concurrent exposure model of environmental pollutants, the principal findings of our study were that birth weight was associated with ΣPCB concentrations in the male and female newborns, and also with THg concentrations in the male ones. However, the significant relation to lead was not seen, probably not only because of low lead levels but also the extremely narrow range of lead exposure, as compared to the values reported previously [ 2 6 ]; whereas, Taylor and coworkers could not find any evidence suggesting a dose–response relationship either in 4190 births (median of maternal blood lead, 3.40 μg/dL; range, 0.20 - 19.14 μg/dL) [ 40 ]. In addition, no evidence of multicollinearity problem among ΣPCB, THg, and fish/seafood intake or of interaction between sex and toxic substances on birth weight was suggested, because all the VIFs were less than 2 in the present study [ 39 ].…”
Section: Discussionmentioning
confidence: 70%
“…Given the concurrent exposure model of environmental pollutants, the principal findings of our study were that birth weight was associated with ΣPCB concentrations in the male and female newborns, and also with THg concentrations in the male ones. However, the significant relation to lead was not seen, probably not only because of low lead levels but also the extremely narrow range of lead exposure, as compared to the values reported previously [ 2 6 ]; whereas, Taylor and coworkers could not find any evidence suggesting a dose–response relationship either in 4190 births (median of maternal blood lead, 3.40 μg/dL; range, 0.20 - 19.14 μg/dL) [ 40 ]. In addition, no evidence of multicollinearity problem among ΣPCB, THg, and fish/seafood intake or of interaction between sex and toxic substances on birth weight was suggested, because all the VIFs were less than 2 in the present study [ 39 ].…”
Section: Discussionmentioning
confidence: 70%
“…Nevertheless, the influence of heavy metals on neonatal birth weight has been disputed in the literature. Recent data have also suggest that there is no change in birth weight from heavy metals exposure [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other Study sought to evaluate the relationship between toxic metals, nutrient combinations and birthweight among 275 mother-child pairs found that prenatal blood Pb was associated with lower Birthweight. Essentials elements Fe, Se, Ca and folate did not modify these relations [18].Taylor et al, examinedBlood samples of pregnant women derived from theAvon Longitudinal Study of Parents and Children (ALSPAC) and suggest that an increase of 1 μg/dl was associated with changes in birth weight of −9.93 g, head circumference −0.03 cm and crownheel length −0.05 cm [19].…”
Section: Discussionmentioning
confidence: 99%